The Role Of Parents In Early Childhood Character Education During The Covid-19 Pandemic - Klara Septia Landa; Babang Robandi (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
Character education is a process that never stops. The government may change, but character education must continue. Character education has challenges and problems that must be solved during online learning during Covid-19, namely the misuse of time and smartphones by children, the difficulty of parents dividing their time in accompanying their children, as well as the difficulty of parents meeting online learning facilities are examples of problems caused by the learning process. online. The purpose of this study was to see the influence of the role of parents on the development of early childhood character during the COVID-19 period. The results of the study show that the role of parents in early childhood character education during the Covid-19 pandemic is very influential. It is important for parents to be involved in the learning process at home, providing information, guidance so that children remain in the development of children's character education during this Covid-19 pandemic. Parental war becomes very important in the development of children's character to be ready to face the world in the future.Keywords: the role of parents, character education, early childhood, the Covid-19 pandemic